Pengaruh Brand Activation Terhadap Brand Image Whitelab: Survei pada Pengunjung Unveil the New Whitelab - Lailynisa Fadilla Iswadi; Jamiati KN; Daniel Handoko (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Brand Activation is one of the important things for a brand. Brand Activation is a strategy that companies use by providing real experiences for consumers. So the purpose of this study is to determine whether Brand Activation has an influence on Brand Image. The theory used in this research is the theory of Brand Activation through the Experiential Marketing approach which includes, sense, feel, think, act, and relate experience. While the Brand Image theory used includes brand strength, uniqueness, and excellence. This research uses quantitative methodology with survey method. The population used in this study were visitors to the